Development of an intra-OECS free trade in services policy - Carmichael, Trevor A. ([s.n.] [S.l.], 1996)
Focuses on policy matters with regard to offshore financial services; corporate legislation; bilateral investment treaties; and, environmental management. Reviews existing and proposed legislation specific to freedom of movement and work permits and the ownership of land.